2015
DOI: 10.1038/srep13885
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Monitoring of Transcriptional Dynamics After Lower-Limb Muscle Injury Enables Quantitative Classification of Healing

Abstract: Traumatic lower-limb musculoskeletal injuries are pervasive amongst athletes and the military and typically an individual returns to activity prior to fully healing, increasing a predisposition for additional injuries and chronic pain. Monitoring healing progression after a musculoskeletal injury typically involves different types of imaging but these approaches suffer from several disadvantages. Isolating and profiling transcripts from the injured site would abrogate these shortcomings and provide enumerative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 64 publications
4
26
2
Order By: Relevance
“…Using RNA-seq on the injured tissues and several types of bioinformatics analyses, the investigators found a series of enriched gene sets associated with chemotaxis and inflammation that were followed by pathways associated with excessive extracellular matrix (ECM) deposition and remodeling. These results were in contrast to many muscle regenerative studies 8 , where inflammatory pathways subsided after several days 9 . Instead, VML injury appears to stimulate complement, Wnt and TGF-β signaling in a sustained fashion, which in turn activates fibrosis development.…”
contrasting
confidence: 99%
“…Using RNA-seq on the injured tissues and several types of bioinformatics analyses, the investigators found a series of enriched gene sets associated with chemotaxis and inflammation that were followed by pathways associated with excessive extracellular matrix (ECM) deposition and remodeling. These results were in contrast to many muscle regenerative studies 8 , where inflammatory pathways subsided after several days 9 . Instead, VML injury appears to stimulate complement, Wnt and TGF-β signaling in a sustained fashion, which in turn activates fibrosis development.…”
contrasting
confidence: 99%
“…Indeed, as expected upon exercise training, C1 displayed an increase in OXCAP markers upon PR, reflecting a restoration of the oxidative metabolic machinery. This is corroborated by the decreased expression of oxidative metabolism regulation markers, as a normalization of metabolism‐related mRNA has previously been shown in late‐stage muscle regeneration . Conversely, in C2, oxidative metabolism regulation and OXCAP were statistically unaltered, although oxidative metabolism regulation seemed to increase upon PR.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, the differential regulation of myogenesis is reflected by a differential change in the expression of specific markers. Interestingly, the reduction in the myogenesis markers MYOD1 and CDH15, and induction in MYMK mRNA expression upon PR in C1, was previously shown to be reflective of late‐stage muscle regeneration . Conversely, the apparent increase in MYOD1 and CDH15 mRNA expression, together with only a tendency towards an increase in MYMK upon PR in C2, is reflective of an earlier phase of muscle regeneration .…”
Section: Discussionmentioning
confidence: 90%
“…To gain insights into the healing process after administration of trauma, we performed expression profiling by RNA sequencing (RNA-seq) and small RNA-seq (miRNA-seq) (Aguilar et al., 2015) for both the injured and contralateral tissues for multiple time points (Figure 1), and lumped the datasets into three key stages (early, 3–24 hr; middle, 48–168 hr; late, 336–672 hr). Hierarchical clustering of the RNA-seq data through time revealed clusters up- and downregulated that were associated with different stages of muscle repair and regeneration (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%